Remote characterization of surface slots by enhanced laser-generated ultrasonic Rayleigh waves - Xiao, Jing (2022)
Characterization of surface features is essential in many industrial applications, especially for features with large depths, high aspect ratios or under extreme conditions. This work presents a non-contact method to characterize surface slots with large lengths using ultrasonic Rayleigh waves generated by a pulsed laser. A delay-and-sum superposition technique is applied to enhance the signal to noise ratio of transmitted Rayleigh waves. The length of the slot can be calculated from the time-of-flight information of Rayleigh waves without any prior knowledge of its orientation, width or aspect ratio. Both numerical simulations and experiments are conducted to demonstrate the proposed method, showing excellent performance. Furthermore, mode conversion has been studied to understand its impact on the reconstruction accuracy. Given the non-contact feature of the laser ultrasonic technique, the proposed method provides a simple and feasible avenue for the rapid characterisation of normal and angled surface features with high aspect ratio in extreme environments.